Operationality of the CSR strategy: Approaches and Impact on the performance of the company - BELAKBIRA, Faycel; Nafzaoui, Mohammed Achraf (Revue Internationale des Sciences de Gestion, 2021)
In the majority of available literature on CSR, the link between the implementation of such as model on a company and its impact on it has been insufficiently studied. We propose in this research to identify the integration components of a CSR strategy and its influence on the competitiveness and attractiveness of a company through conducting an exploratory analysis of Veolia Management System.